Improved extraction of resveratrol and antioxidants from grape peel using heat and enzymatic treatments. (19th March 2019) - Averilla, Janice N; Oh, Jisun; Wu, Zhexue; Liu, Kwang‐Hyeon; Jang, Chan Ho; Kim, Hyo Jung; Kim, Jae‐Sik; Kim, Jong‐Sang
Abstract: BACKGROUND: Resveratrol, an extensively recognized phytochemical that belongs to the stilbene family, is abundant in grape peel which is discarded as a by‐product during grape juice processing. RESULTS: In this study, we established that pre‐heating grape peel above 75 °C significantly improved the extractability of resveratrol and its glucoside piceid. In particular, thermal heating of grape peel at 95 °C for 10 min, followed by treatment with a mixture of exo ‐1, 3‐β‐glucanase and pectinases at 50 °C for 60 min, dramatically increased the conversion of piceid into resveratrol and the overall extractability of this phytochemical by 50%. Furthermore, thermal pre‐treatment promoted a substantial increase in the total phenol, flavonoid, and anthocyanin concentrations in the grape peel extract. Ultimately, resveratrol‐enriched grape peel extract significantly augmented the antioxidant response in vitro, possibly by attenuating the accumulation of intracellular reactive oxygen species via the Nrf2 signaling pathway. CONCLUSION: The method developed in this study for preparing grape peel extract introduces a potential low‐cost green processing for the industrial fortification of food products with resveratrol and other health‐beneficial antioxidants. © 2019 Society of Chemical Industry